Sea level controls terrigenous sediment provenance evolution in the Okinawa Trough since the Last Glacial Maximum - Mingyu Zhang; Libo Wang; Jingtao Zhao; Yong Zhang; Hao Tian; Shanshan Chen; Bangqi Hu; Jing Kan; Fuyu Wu; Xiting Liu (Frontiers in Marine Science, 2026)
The Okinawa Trough (OT), a typical back-arc basin in the western Pacific, preserves continuous sedimentary records since the Quaternary, making it a critical area for investigating sea-level changes, source-to-sink processes, and paleoclimate evolution. However, the controlling mechanisms of terrestrial input to the trough since the Last Glacial Maximum (LGM) remain insufficiently understood. This study conducted major element geochemical analysis on core C1624 from the southern part of the middle OT, combined with AMS 14 C dating, grain size, and mineralogical data, to reconstruct the evolution and dominant controls of terrestrial input since the LGM. Principal component analysis (PCA) indicates that the sediments in the study area are primarily composed of a mixture of two end-members: terrigenous detritus and marine biogenic carbonate. The ratios of TFe 2 O 3 /Al 2 O 3 and CaO/Al 2 O 3 were adopted as reliable proxies for terrestrial input and biogenic contribution, respectively. The results reveal a three-stage response of terrestrial input to sea-level changes since the LGM: Stage 1 (25.4–11.6 ka BP), during low sea-level stands, the paleo-Changjiang river system extended to the outer shelf, supplying the dominant sediment source; Stage 2 (11.6–8.7 ka BP), characterized by rapid sea-level rise, witnessed a transition in provenance from the Changjiang to Taiwan-derived materials, accompanied by a sharp decrease in terrestrial input; Stage 3 (8.7–0 ka BP), with the establishment of modern circulation patterns, Taiwan-sourced materials became predominant. This study demonstrates that sea-level changes on glacial-interglacial scales are the fundamental factor reshaping the depositional pattern and driving provenance transitions in the middle OT. These findings provide a new case for understanding the response of marginal sea sediment source-to-sink processes to global climate change.